Endophytic fungi: a reservoir of antibacterials - Deshmukh, Sunil K.; Verekar, Shilpa A.; Bhave, Sarita V. (Frontiers in Microbiology, 2015)
Multidrug drug resistant bacteria are becoming increasingly problematic particularly in the undeveloped countries of the world. The most important microorganisms that have seen a geometric rise in are Methicillin resistant Staphylococcus aureus, Vancomycin resistant Enterococcus faecium, Penicillin resistant Streptococcus pneumonia and multiple drug resistant tubercule bacteria to name a just few. New drug scaffolds are essential to tackle this every increasing problem. These scaffolds can be sourced from nature itself. Endophytic fungi are an important reservoir of therapeutically active compounds. This review attempts to present some data relavent to the problem. New, very specific and effective antibiotics are needed but also at the affordable price!!!. Herculean task for researcher all over the world. In the Asian subcontinent indigenous therapeutics that has been practiced over the centuries such as Ayurveda that has been effective as ‘handed down data’ in family generations. May need a second, third and more “in-depth investigations?”